6(a+2)+10=16-a+27

Simple and best practice solution for 6(a+2)+10=16-a+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(a+2)+10=16-a+27 equation:


6(a+2)+10=16-a+27

We simplify the equation to the form, which is simple to understand
6(a+2)+10=16-a+27

Reorder the terms in parentheses
+(+6a+12)+10=16-a+27

Remove unnecessary parentheses
+6a+12+10=+16-a+27

We move all terms containing a to the left and all other terms to the right.
+6a+1a=+16+27-12-10

We simplify left and right side of the equation.
+7a=+21

We divide both sides of the equation by 7 to get a.
a=3

See similar equations:

| 8c-9=7c+4 | | sin(0.5x)=-1.5 | | 2t+1=t+8 | | 2(a+1)=14+a | | R=60q+q^2 | | 3t+1=t+8 | | =60Q-Q^2 | | xsquare+37x+210=0 | | 14=2(a-2) | | iz^2-3z-2i=0 | | iz^2+3z-2i=0 | | 3t+3=t+8 | | 14+a=2(a-4) | | 10x^3-7x-3=0 | | kx^2-kx^2=-1 | | X+35=6x | | 4-7a+15-8a-21= | | 1.5x+4=0.25x-3 | | 16h^4-8h^2+1=0 | | 0.875t-2=0.375t+9 | | 2(4x-1)+3x=-13o | | 22.67647059= | | 6=4*-10 | | y=29 | | 5x-4=x+32 | | 5x^4+16x^3+12x^2=0 | | 27a^3+64= | | x^2+3x+88=0 | | x(x+3)=88ft^2 | | 2x-9=57 | | 4(-2c+1)=3c-18 | | 28x^2-x-15=0 |

Equations solver categories